﻿Detection and description of four Vespa mandarinia (Hymenoptera, Vespidae) nests in western North America - Chris Looney; Brant Carman; Jenni Cena; Cassie Cichorz; Vikram Iyer; Jessica Orr; Nathan Roueché; Karla Salp; Jacqueline M. Serrano; Landon Udo; Paul van Westendorp; Telissa M. Wilson; et al. (Journal of Hymenoptera Research, 2023)
Vespa mandarinia Smith 1852 is a semi-specialized predator of other social Hymenoptera and one of the two largest species of Vespa. Several individuals of this predatory wasp were detected in Canada and the United States in 2019, including an entire nest that was located and destroyed on Vancouver Island, British Columbia. The Washington State Department of Agriculture and the United States Department of Agriculture’s Animal and Plant Health Inspection Service have collaborated to survey Washington State for V. mandarinia since 2020, using traps staffed by agency personnel, collaborators from local governments and nongovernmental organizations, and the general public. Trap data and public reports were used to select sites for live-trapping or net surveys, and live hornets captured in these efforts were subsequently collected and fitted with radio tags to locate nests. The survey ultimately led to the discovery of a V. mandarinia nest in October 2020, and three nests in August and September 2021. All of the nests were located within in red alder trees (Alnus rubra), with one just above the ground in a standing dead tree, and the other three in cavities ~2 to 5 meters above the ground in living trees. The number of combs in each nest varied between four and ten, cells between 418 and 1,329, and total hornets per nest between 449 and 1,474 (including immature and mature stages). Together, the four nests indicate an incipient population of V. mandarinia in the Cascadia region, and ongoing action by local, state, provincial, and federal governments, and residents of both countries is required to avoid the establishment of this exotic species in the region.